O uso do Geogebra no ensino da geometria analítica: estudo da circunferência - Oliveira, Carlos André Neiva de (2013)
This work refers to the GeoGebra application use for teaching analytic geometry. In this work it was made a guidelines approach about the PCNEM, to teach and discuss the use of the technologies in analytic geometry about computers, software and mathematics. It was made a brief history about the applications testing some tools checking if they are useful to develop circumference studies to apply in high school rst grades using that GeoGebra study.